Relative Superiority of the Interaction Potential Models for Lattice Energy Calculation of Alkali Metal Halide Crystals - Kumar Singh, Anil; Kumar Sinha, Arun (Asian Journal of Chemistry, 2016)
The non-coulombic nature of the repulsive energy term Ψ(r) in the total potential energy function symbol f(r) for a diatomic ionic crystal has been of much interest for the last nine decades. Various workers have proposed it either as the inverse power function, exponential function or logarithmic function. A critical review of the potential energy functions proposed earlier has been presented. It was found that no potential model can be claimed as a universal model. However, the relative superiority of these potential models in the calculation of lattice energy of 20 alkali metal halide crystals has been reported.